Increasing The Professionalism of Tourism Village Management in The Digitalization Era for Sustainable Tourism at Penglipuran Village - Putu Herny Susanti; IB Putu Wira Diana; Gede Agus Deny Permana; IB Nyoman Weda; I Putu Mega Adi Adnyana; Abirama Sudayasa (CV. Multi Kreasi Media, 2025)
The COVID-19 pandemic has profoundly affected the global tourism industry, including Penglipuran Village as one of Bali’s flagship destinations. This community service program aims to enhance management effectiveness, optimize local human resources, and strengthen the village’s competitiveness in the digital era. The program was implemented through workshops, interactive discussions, mentoring, and the signing of collaboration agreements (MOU, MOA, and IA). The results indicate improved community understanding of tourism digitalization, strengthened MSMEs through digital marketing based on local wisdom, and the development of a more professional homestay management system. The outputs, including copyrighted documentary videos and strategic partnerships, demonstrate the program’s sustainability. Continuous training, digital technology optimization, and culture-based branding are expected to position Penglipuran as a model for sustainable tourist villages in Indonesia.